Athens in the spring of 1896 - Alexey Butovsky (National University of Physical Education and Sport of Ukraine, 2016)
The article presents the reminiscences about the first modern Olympic Games, which were held in 1986 in Athens, written by our outstanding compatriot A. D. Butovsky, who was one of the initiators of the revival of the modern Olympic movement of the late 19th century, the member of the first International Olympic Committee, a prominent expert in the field of theory and methodology of physical education and of the system for training of professionals in physical education and sports in military and civilian educational institutions.